2004
DOI: 10.1016/s0140-6736(04)17225-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-trimoxazole prophylaxis on morbidity, mortality, CD4-cell count, and viral load in HIV infection in rural Uganda

Abstract: SummaryBackground Prophylaxis with co-trimoxazole (trimethoprim-sulphamethoxazole) is recommended for people with HIV infection or AIDS but is rarely used in Africa. We assessed the effect of such prophylaxis on morbidity, mortality, CD4-cell count, and viral load among people with HIV infection living in rural Uganda, an area with high rates of bacterial resistance to co-trimoxazole.Methods Between April, 2001, and March, 2003, we enrolled, and followed up with weekly home visits, 509 individuals with HIV-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
232
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(252 citation statements)
references
References 30 publications
16
232
4
Order By: Relevance
“…It has a broad-spectrum prophylactic action against common bacterial pathogens, Pneumocystis jirovecii (formerly Pneumocystis carinii) , and protozoa such as Plasmodium spp and Isospora belli. Randomised controlled trials (RCTs) 9,10 and studies with historical controls [11][12][13][14][15][16] in HIVinfected African adults consistently show signifi cant benefi ts in survival for those receiving co-trimoxazole prophylaxis. These improvements in survival have been accompanied by substantial reductions of severe disease events and the number of hospital admissions linked to invasive bacterial disease, pneumonia, malaria, and diarrhoea, although disease-specifi c benefi t has varied between studies.…”
Section: Benefi Ts Of Co-trimoxazole Prophylaxis In Hivinfected Infanmentioning
confidence: 99%
See 2 more Smart Citations
“…It has a broad-spectrum prophylactic action against common bacterial pathogens, Pneumocystis jirovecii (formerly Pneumocystis carinii) , and protozoa such as Plasmodium spp and Isospora belli. Randomised controlled trials (RCTs) 9,10 and studies with historical controls [11][12][13][14][15][16] in HIVinfected African adults consistently show signifi cant benefi ts in survival for those receiving co-trimoxazole prophylaxis. These improvements in survival have been accompanied by substantial reductions of severe disease events and the number of hospital admissions linked to invasive bacterial disease, pneumonia, malaria, and diarrhoea, although disease-specifi c benefi t has varied between studies.…”
Section: Benefi Ts Of Co-trimoxazole Prophylaxis In Hivinfected Infanmentioning
confidence: 99%
“…17 Many of the studies showing benefi t have been in communities where in-vitro co-trimoxazole resistance to common bacterial isolates is already high. 14,[16][17][18] It is well recognised that P jirovecii is a common cause of pneumonia and death in HIV-infected infants. [19][20][21][22] The introduction of routine co-trimoxazole prophylaxis for infants at risk of HIV infection in several countries has been very eff ective in preventing P jirovecii pneumonia, which could in itself prevent a third to a half of all HIVrelated deaths in African infants.…”
Section: Benefi Ts Of Co-trimoxazole Prophylaxis In Hivinfected Infanmentioning
confidence: 99%
See 1 more Smart Citation
“…Cotrimoxazole prophylaxis, which reduces mortality; decreases the risk of diarrhoea, malaria, and bacteremia; and potentially benefits CD4 cell count and viral load among people with HIV living in Africa (Badri, 2001;Castetbon, 2001;Mermin, 2004;Witkor, 1999). Cotrimoxazole prophylaxis has been recommended for daily use by adults and children with HIV by the Joint United Nations Program on HIV/ AIDS (UNAIDS) and the World Health Organization (WHO, 2006) and is recommended by the Ugandan Ministry of Health for all individuals living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…22 A study evaluating the effect of co-trimoxazole for PJP prophylaxis in Uganda demonstrated that the number needed to treat (prophylaxis) per life saved was 2.6 in individuals with a CD4 cell count below 200 cells/mm 3 compared with 8.3 for all participants in the study. 23 Therefore despite the risk of misclassification of the immune status using this study's methods, when weighted against long waiting periods for measured CD4 count results in resource-limited settings, primary prophylaxis with co-trimoxazole may be advocated using this method due to the high mortality rate associated with PJP. Whilst early initiation of ART is imperative, as a practical indicator of ART initiation further prospective studies are required before the use of this method can be advocated.…”
Section: Discussionmentioning
confidence: 99%